Analysis of Capasitor Bank Installation for Power Quality Improvement at PT. Sunrise Steel - Reza Sarwo Widagdo Widagdo; Gatut Budiono; Mohammad Irfandi Novianto (Wahana, 2023)
The large number of inductive loads used, namely 3-phase induction motors and welding machines, has caused a low power factor in the electrical system at PT. Sunrise Steel. In this industry there are 2 production sites for coated steel named Continous Galvalume Line 1 and Continous Galvalume Line 2. There are 6 transformers that supply power to the two places, but there are 2 transformers that have a very low power factor, where Transformer 1 (Continous Galvalume Line 2) a capacitor bank has been installed but the power factor is still low, which is 0.67 and Transformer 3 (Continous Galvalume Line 1) is 0.66. The addition of Capacitor Bank is of course very much needed to increase the value of the power factor in the two electrical systems. This research targets an increase in power factor to 0.98, where Transformer 1 (Continuous Galvalume Line 2) requires the addition of a 17.831 uF capacitor and Transformer 3 (Continous Galvalume Line 1) requires a 2948,81 uF capacitor using an automatic compensation technique. The compensation method used in both is the global compensation method, a capacitor will be installed on each main LVMDP. ETAP Power Station software is used to simulate the results of installing capacitor banks.